The Utilization of Artificial Intelligence for Financial Inclusion and Business Sustainability Among MSME Operators: Literature Review - Sudrajat, Bagas; Johan, Destarika Irene; Kusumawardhani, Amie; Indriani, Farida (Research Horizon, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are a business sector that plays an important role in Indonesia's economy. MSME actors often face challenges in the sustainability of their businesses, both in terms of innovation and competitiveness, especially in the current digital era, which requires MSME actors to understand rapidly evolving technology. In the current technological development, the utilization of Artificial Intelligence (AI) can assist in various aspects of daily life. MSME actors can develop their businesses with the help of AI for decision-making and to take part in the financial sector, which ultimately improves business sustainability and more broadly increases economic growth. However, AI has not been widely utilized by MSMEs in Indonesia. The research method employed in this study is a literature review, which is a review or summary of previous research findings on the utilization of AI for financial inclusion and business sustainability in the MSME sector. This study presents an overview of the benefits and challenges of AI for MSME actors, as well as its impact on improving business sustainability and increasing economic growth.